Variational Learning in Child L2 Acquisition? Comprehension of Verbal Agreement in Spanish and English. Issue 3 (2nd July 2020) - Morales Reyes, Alexandra; Montrul, Silvina
ABSTRACT: The Spanish verbal system offers more evidence for agreement and tense than English, where morphological evidence is less robust. With a focus on the comprehension of verbal agreement morphology by child second (L2) learners of Spanish and English, we extend the Variational Learning account to L2 acquisition to investigate whether the abundance of morphological evidence for subject agreement in the target language contributes to the rate of acquisition. Participants were 32 Spanish-speaking L2 learners of English and 32 English-speaking L2 learners of Spanish ages 7;5–10;11. The children's comprehension of verb agreement morphology in Spanish and in English was assessed with an off-line picture-sentence matching task in each language. The results show higher accuracy comprehending agreement for the children learning L2 Spanish compared to the children learning L2 English. This finding is consistent with a probabilistic approach to morphological learning and the role of morphological typology in the rate of acquisition.